2018
DOI: 10.4236/ojas.2018.83017
|View full text |Cite
|
Sign up to set email alerts
|

Age and Gender Dependent Amino Acid Concentrations in the Feather, Feather-Free and Whole Empty Body Protein of Fast Growing Meat-Type Chickens

Abstract: Two consecutive growth experiments with meat-type chickens (Ross 308) were conducted in order to quantify the age-dependent amino acid (AA) content in the whole body protein of male and female birds based on experimental data of the feather and feather-free body protein fractions. Birds were reared under uniform housing and feeding conditions (floor pens, 15 pens per gender, 5 birds per pen) during the starter (day 1 to 22) and grower period (day 22 to 36). Both the starter and grower diet based on corn, wheat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 48 publications
(48 reference statements)
0
5
0
Order By: Relevance
“…Therefore, protease supplementation could increase the concentration of free amino acids in breast muscle. It has been reported that the levels of total amino acids in serum, liver, feather, and carcass can reflect the amino acids utilization (Kaczmarek et al 2014;Azzam et al 2015Azzam et al , 2017Dong et al 2016;Morales et al 2017;Wecke et al 2018;Middendorf et al 2019). In addition, amino acids concentrations in carcass could be used to determine amino acid requirements accurately in broiler diets (Stilborn et al 2010;Abd El-Moneim et al 2019;Saleh et al 2019b).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, protease supplementation could increase the concentration of free amino acids in breast muscle. It has been reported that the levels of total amino acids in serum, liver, feather, and carcass can reflect the amino acids utilization (Kaczmarek et al 2014;Azzam et al 2015Azzam et al , 2017Dong et al 2016;Morales et al 2017;Wecke et al 2018;Middendorf et al 2019). In addition, amino acids concentrations in carcass could be used to determine amino acid requirements accurately in broiler diets (Stilborn et al 2010;Abd El-Moneim et al 2019;Saleh et al 2019b).…”
Section: Discussionmentioning
confidence: 99%
“…However, Gous et al [42] and Bonato et al [67] have postulated that the rate of feather protein gain during growth is higher than that for body protein. As already discussed [4] [5], the partitioning of protein in muscle tissues, organs and feathers is differentiates as age advances.…”
Section: Discussionmentioning
confidence: 85%
“…4 Final body weight of male birds was determined 1 d earlier (see Table 3). 5 Starter period (d 1 -d 22). 6 Grower period (d 22 -d 36).…”
Section: Resultsmentioning
confidence: 99%
“…(2017) estimated digestible Lys requirements of broilers from 28 to 42 d as 0.879% for BWG, and 0.891% for breast meat yield using a linear broken-line model, which is comparable to the results in the present study. The greater requirement for breast muscle weight compared with BWG may be attributed to the body composition change to more body fat contents as birds aged ( Baker, 1986 ; Wecke et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%